Four new species and additional records of the genus Stenus of southern Africa (Coleoptera: Staphylinidae: Steninae) - Janák, Jiří (Zootaxa, 2022)
Four species of the genus Stenus Latreille, 1797: S. hippoamicus Janák, sp. nov., S. rugosellus Janák, sp. nov., S. spiniferoides Janák, sp. nov. and S. volkerputhzianus Janák, sp. nov. of South Africa are described, illustrated and distinguished from related species. Additional records of the genus Stenus Latreille, 1797 of southern Africa are presented.